Social-Emotional Development of Children in Asia: A Systematic Review - Yong, Geok Har *; Lin, Mei Hua *; Toh, Teck Hock; Marsh, Nigel V. (MDPI, 2023)
There has been growing interest in the social-emotional development of children. However, the social-emotional development of children in Asia remains a knowledge gap. This systematic review identifies and summarizes existing studies on children’s social-emotional development in Asia. We conducted a systematic review using the Guidelines for Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). We reviewed 45 studies that met the inclusion criteria, and they were from 12 Asian countries, primarily the East Asia region (China and Hong Kong). Most of the studies were cross-sectional in design (n = 28, 62.2%). Six themes emerged, including (a) social-emotional development (overall) (n = 24, 53.3%); (b) social competence (n = 7, 15.6%); (c) emotional development (n = 5, 11.1%); (d) social-emotional learning (n = 3, 6.7%); (e) problem behavior (n = 3, 6.7%); (f) self-regulation (n = 2, 4.4%); and (g) both social-emotional learning and problem behavior (n = 1, 2.2%). The findings highlighted the paucity of studies, the need for examining more diverse variables in a similar population, and the low quality of intervention studies in social-emotional research in Asia. Research gaps indicate the need for more social-emotional and ethnocultural studies in other Asian regions. Parent and teacher knowledge of children’s social-emotional functioning should be examined more closely in future research.